Investigation of pore water and soil extraction tests for characterizing the fate of poorly soluble metal-oxide nanoparticles. (March 2021) - Rodrigues, Sandra; Bland, Garret D.; Gao, Xiaoyu; Rodrigues, Sónia M.; Lowry, Gregory V.
Abstract: Here we compared the efficiency of Cu extraction (dissolved + particulate) from two soils dosed with CuO nanoparticles (NPs) at 50 or 250 mg kg −1 by pore water collection, and single- and multi-step soil extraction tests. Pore water collection recovered low levels of Cu (<0.18%, regardless of soil type or Cu dose). Single soil extraction by either CaCl2 or DI water led to higher Cu recovery than pore water collection, but still <3% of total dose. These methods were useful for assessing the labile Cu ions pool. This fraction is controlled by Cu 2+ dissolved from CuO NPs and it varies with time and soil type. Particulate Cu was poorly retrieved (<0.7%) by pore water extraction and by single-step soil extraction using CaCl2 solution or water. Multi-step extraction including dispersing and metal-chelating agents allowed for simultaneous characterization of dissolved Cu (total ionic Cu 2+, 24–49% of dosed Cu), extractable CuO NPs (reversibly attached, 15–26% of dosed Cu), and non-extractable CuO NPs (irreversibly attached, 36–50% of dosed Cu), and it could describe the aging of NPs along 30 d. This method extracted a significantly higher concentration of Cu than pore water collection and was less sensitive to method parameters (e.g. filtration). This multi-step method can reduce pore water extraction-related factors that may confound the interpretation of environmental exposure data in NPs studies, and describe upper limits of both exchangeable Cu 2+ and dispersible CuO NPs in soil that can potentially become bioavailable to plants and organisms and thus provide a sounder basis for risks evaluations. Graphical abstract: Image 1 Highlights: Pore water collection methods have limited capacity to extract CuO NPs from dosed soil. Both filtration and centrifugation affect the recovery of NPs from soil pore-water. A multi-step extraction retrieved both ionic Cu and reversibly attached CuO NPs. This method characterizes dissolution, attachment, and aging of CuO NPs in dosed soil.